Novo método não invasivo com ácido hialurônico para rejuvenescimento facial - estudo piloto - Morais, Bianca Silva de (Universidade Federal de São Carlos, 2025)
One of the visible signs of the skin aging process is related to facial wrinkles. These wrinkles arise due to several factors, ranging from lifestyle to muscle strength during facial expressions. This study aims to investigate the behavior of facial wrinkles after non-invasive treatment with hyaluronic acid. The research was conducted through an experimental study that involved the application of three sessions of hyaluronic acid with shockwave equipment, and the treatment was proposed for different skin phototypes. The methodology used is based on the clinical evaluation of the skin (initial, after each session, and during follow-ups for 60 days), assessment of skin moisture and oiliness, and photographic records at the following times: initial, after each session, and during follow-ups for 60 days. The results indicated the efficacy of using hyaluronic acid and shock waves for treating facial wrinkles and improving skin characteristics, such as wrinkle smoothing in the frontal region, tissue tone, softness, and skin hydration. The results showed that the groups that combined HA+EQ (Group 1 and Group 3) were the patients who presented the best results in terms of increased skin hydration, improved brightness, texture, and greater smoothing of wrinkles and facial lines. It is concluded that, although there are other treatments for rejuvenation that improve facial appearance, the prevention and application of hyaluronic acid and shock waves have an effect duration of 60 days. This protocol provides smoothing of facial wrinkles and, consequently, in addition to rejuvenating the skin tissue, allows the treatment to be effective and completely painless for the patient.
New non-invasive method with hyaluronic acid for facial rejuvenation – pilot study
Keywords: Ácido hialurônico; Ondas de choque; Rugas faciais; Tratamento não invasivo; Hyaluronic acid; Shock waves; Facial wrinkles; Non-invasive treatment; CIENCIAS EXATAS E DA TERRA::FISICA::AREAS CLASSICAS DE FENOMENOLOGIA E SUAS APLICACOES::OTICA